Model‐based assessments of CYP3A‐mediated drug‐drug interaction risk of milademetan - Ying Hong; Tomoko Ishizuka; Akiko Watanabe; Masaya Tachibana; Mark Lee; Hitoshi Ishizuka; Frank LaCreta; Malaz Abutarif (Wiley, 2021)
Abstract Milademetan is a small‐molecule inhibitor of murine double minute 2 (MDM2) that is in clinical development for advanced solid tumors and hematological cancers, including liposarcoma and acute myeloid leukemia. Milademetan is a CYP3A and P‐glycoprotein substrate and moderate CYP3A inhibitor. The current study aims to understand the drug‐drug interaction (DDI) risk of milademetan as a CYP3A substrate during its early clinical development. A clinical DDI study of milademetan (NCT03614455) showed that concomitant administration of single‐dose milademetan with the strong CYP3A inhibitor itraconazole or posaconazole increased milademetan mean area under the curve from zero to infinity (AUCinf) by 2.15‐fold (90% confidence interval [CI], 1.98-2.34) and 2.49‐fold (90% CI, 2.26-2.74), respectively, supporting that the milademetan dose should be reduced by 50% when concomitantly administered with strong CYP3A inhibitors. A physiologically‐based pharmacokinetic (PBPK) model of milademetan was subsequently developed to predict the magnitude of CYP3A‐mediated DDI potential of milademetan with moderate CYP3A inhibitors. The PBPK model predicted an increase in milademetan exposure of 1.72‐fold (90% CI, 1.69-1.76) with fluconazole, 1.91‐fold (90% CI, 1.83-1.99) with erythromycin, and 2.02‐fold (90% CI, 1.93-2.11) with verapamil. In addition, it estimated that milademetan's original dose (160 mg once daily) could be resumed from its half‐reduced dose 3 days after discontinuation of concomitant strong CYP3A inhibitors. The established PBPK model of milademetan was qualified and considered to be robust enough to support continued development of milademetan.